Innovative approaches to combat antibiotic resistance: integrating CRISPR/Cas9 and nanoparticles against biofilm-driven infections - Abolfazl Saffari Natanzi; Mohsen Poudineh; Elham Karimi; Azad Khaledi; Hamed Haddad Kashani (BMC Medicine)
Abstract The increasing prevalence of antibiotic-resistant bacterial infections is a major global health concern, with biofilms playing a key role in bacterial persistence and resistance. Biofilms provide a protective matrix that limits antibiotic penetration, enhances horizontal gene transfer, and enables bacterial survival in hostile environments. Conventional antimicrobial therapies are often ineffective against biofilm-associated infections, necessitating the development of novel therapeutic strategies. The CRISPR/Cas9 gene-editing system has emerged as a revolutionary tool for precision genome modification, offering targeted disruption of antibiotic resistance genes, quorum sensing pathways, and biofilm-regulating factors. However, the clinical application of CRISPR-based antibacterials faces significant challenges, particularly in efficient delivery and stability within bacterial populations. Nanoparticles (NPs) present an innovative solution, serving as effective carriers for CRISPR/Cas9 components while exhibiting intrinsic antibacterial properties. Nanoparticles can enhance CRISPR delivery by improving cellular uptake, increasing target specificity, and ensuring controlled release within biofilm environments. Recent advances have demonstrated that liposomal CRISPR-Cas9 formulations can reduce Pseudomonas aeruginosa biofilm biomass by over 90% in vitro, while gold nanoparticle carriers enhance editing efficiency up to 3.5-fold compared to non-carrier systems. These hybrid platforms also enable co-delivery with antibiotics, producing synergistic antibacterial effects and superior biofilm disruption. Additionally, they can facilitate co-delivery of antibiotics or antimicrobial peptides, further enhancing therapeutic efficacy. This review explores the synergistic integration of CRISPR/Cas9 and nanoparticles in combating biofilm-associated antibiotic resistance. We discuss the mechanisms of action, recent advancements, and current challenges in translating this approach into clinical practice. While CRISPR-nanoparticle hybrid systems hold immense potential for next-generation precision antimicrobial therapies, further research is required to optimize delivery platforms, minimize off-target effects, and assess long-term safety. Understanding and overcoming these challenges will be critical for developing effective biofilm-targeted antibacterial strategies. Graphical Abstract